Ecological Risk Evaluation of Inorganic Contaminants and Microbial Activities in Obunagha River, Bayelsa State, Nigeria - Onwugbuta, Godpower Chukwuemeka; Ayafa, Timinipre Comfort (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2025)
The study was carried out to evaluate the Ecological Risk Assessment of Inorganic Contaminants and Microbial activities of Obunagha River in Bayelsa State. Eight water samples were collected from four sampling points in the Gbarain Clan community. The analysis included heavy metal samples of Zinc, Manganese, Cadmium, Chromium, Nickel, Lead, and Copper, and some Microbial assays. Pollution Indices such as Contamination Factor, Pollution Load Index, Heavy Metal Potential Ecological Risk Coefficient, Potential Contamination Index, and Quantitative Microbial contamination were assessed. The Pollution Load Index (PLI) indicated a moderate pollution level for all metals, with Zn (1.3685), Mn (1.3685), Cd (1.26425), Cr (0.9455), Ni (1.291), Pb (1.01875), and Cu (0.99325). The Pollution Contamination Index (PCI) values of Obunagha River reveal significant contamination, especially for Nickel and Lead. The ecological risk landscape is complex, with moderate levels of zinc, manganese, and Cadmium, and varying degrees of contamination for Chromium, Nickel, Lead, and Copper. Microbial activity assessment in water samples indicated potential health risks associated with Vibrio (2.25 x 102 cfu/mL), E. coli (1 x 101 cfu/mL), Salmonella (3.825 x 102 cfu/mL), and Shigella (6 x 101 cfu/mL). This study becomes evident that the samples collected exhibit significantly higher bacterial concentrations, particularly for Salmonella and Shigella, which indicates a higher potential risk to both humans, animals, and aquatic biota. It is therefore, recommended that further study should be carried out to determine the tidal flow, geological features and its effect on aquatic biota such as fish.